Physician-modified endograft in ruptured aortic arch - Jędrzejczak, Tomasz; Żołnierczuk, Michał; Molski, Maciej; Rynio, Paweł; Rybicka, Anita; Kazimierczak, Arkadiusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
We present the case of a 27-year-old motorcyclist after a multi-organ trauma. He suffered a rupture of the aortic arch located in zone 2 and was disqualified from surgical replacement of the aortic arch due to active bleeding from parenchymal organs. Instead, he was provided with a physician-modified endograft (PMEG) to complete fenestrated thoracic endovascular aortic repair as a damage control procedure. No reports in the world literature are found regarding the use of PMEG technology in truly ruptured post-traumatic pseudo-aneurysm on the border of zone 1 and 2 of the aortic arch in emergency settings. The surgery provided temporary supply of the aorta and allowed all of the other surgical and orthopedic procedures to be completed. Endovascular treatment of aortic arch damage with PMEG is possible and can be effectively used for urgent indications when an open operation is not possible.